A Multisite Case Study of Caregiver Advise, Record, Enable Act Implementation. (6th February 2019) - Leighton, Cassandra; Fields, Beth; Rodakowski, Juleen L; Feiler, Connie; Hawk, Mary; Bellon, Johanna E; James, A Everette
Abstract: Background and Objectives: The Commonwealth of Pennsylvania passed the Caregiver Advise, Record, Enable (CARE) Act on April 20, 2016. We designed a study to explore early implementation at a large, integrated delivery financing system. Our goal was to assess the effects of system-level decisions on unit implementation and the incorporation of the CARE Act's three components into routine care delivery. Research Design and Methods: We conducted a multisite, ethnographic case study at three different hospitals' medical–surgical units. We conducted observations and semi-structured interview to understand the implementation process and the approach to caregiver identification, notification, and education. We used thematic analysis to code interviews and observations and linked findings to the Promoting Action on Research Implementation in Health Services framework. Results: Organizational context and electronic health record capability were instrumental to the CARE Act implementation and integration into workflow. The implementation team used a decentralized strategy and a variety of communication modes, relying on local hospital units to train staff and make the changes. We found that the system facilitated the CARE Act implementation by placing emphasis on the documentation and charting to demonstrate compliance with the legal requirements. Discussion and Implications: General acute hospitals will be making or have made similar decisions on how to operationalize the regulatory components and demonstrate compliance with the CARE Act. This study can help to inform others as they design and improve their compliance and implementation strategies.